DISKURSUS KESETARAAN GENDER DALAM PERSPEKTIF HUKUM ISLAM; MENUJU RELASI LAKI-LAKI DAN PEREMPUAN YANG ADIL DAN SETARA - Mudaris, Hudan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
One of global issue that attracted our attention nowadays is gender issue. This gender issue has its momentum from manydiscourses at seminars, locally or international. The thriving of gender inequality, that produced injustice and even violence to women,basically is a social and culture construct that built from complex process. And one of fact is religious texts suspected as factors that maintainthis injustice to women.